Workstyle: development of a measure of response to work in those with upper extremity pain. - Feuerstein M; Nicholas RA; Huang GD; Haufler AJ; Pransky G; Robertson M (Journal of Occupational Rehabilitation, 2005)
Workstyle or the behavioral, cognitive, and physiological response that can occur in some individuals to increases in work demands has been proposed to help explain the link between ergonomic and psychosocial factors in the exacerbation of work-related upper extremity symptoms. Currently, there is no measure of this construct, hindering research on its potential link to work related upper extremity problems in the workplace. The present study describes the development and psychometric properties of a measure of workstyle. Questionnaire items reflecting dimensions of workstyle as per the original conceptualization were generated primarily through focus groups with office workers and separate groups held with occupational physicians, physical therapists, occupational health psychologists, and experts in ergonomics, behavioral science, and human factors. Items created through this process were then administered to 282 symptomatic and asymptomatic office workers. Measures of job stress, ergonomic risk, upper extremity symptoms, and functional limitations were also obtained. The workstyle questionnaire was divided into two broad dimensions: Characteristic responses to work and Response to increased work demands. The scale development process as indicated by factor analysis yielded subscales that are theoretically consistent with the workstyle construct. These subscales include: working through pain, social reactivity at work, limited workplace support, deadlines/pressure, self imposed work pace/workload, breaks, mood, pain/tension, autonomic response, and numbness tingling. The internal consistency of these subscales varied from 0.61 to 0.91, n = 282 while the test-retest (3 weeks) reliability for the various subscales ranged from r = 0.68 to 0.89, n = 143. A total workstyle score was computed that excluded the pain/tension and numbness/tingling subscales to avoid circular reasoning in terms of the measure's relationship to outcomes of pain and functional limitations. The total score was stable over time and provided unique variance in relation to traditional measures of job stress. Total workstyle score was significantly associated with higher levels of pain, and greater functional limitations. Dimensions of the workstyle construct were identified. The workstyle measure possesses acceptable psychometric properties in office workers who work with computers. This measure can be used in future studies on the interaction of psychosocial and ergonomic factors in the exacerbation of upper extremity pain and functional limitation.